ANALYSIS OF THE INFLUENCE OF FINANCIAL LITERACY AND RISK PERCEPTION ON INVESTING DECISIONS IN THE MILLINEAL GENERATION IN THE SOCIETY 5.0 ERA - Endah Prawesti Ningrum; Jumarni Jumarni; Teguh Setiawan Wibowo; Nurlia Nurlia; Pilifus Junianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research is motivated by the importance of investment decisions for the millennial generation. This study aims to identify and analyze the effect of financial literacy and risk perception on the investment decisions of the millennial generation in the era of society 5.0. This research method is descriptive with a quantitative approach. The sample in this study was 100 millennial generations who were taken by random sampling. The instrument used is a questionnaire distributed via google form. The instruments used have been tested for validity and reliability. The collected data were analyzed using the classical assumption test and multiple linear regression using SPSS version 23.0. The results of this study explain 1) Financial literacy has a positive and significant effect on the investment decision of the millennial generation in the society 5.0 era, 2) Risk perception has a positive and significant effect on the investment decision of the millennial generation in the society 5.0 era, and 3) Financial literacy and risk perception have a positive effect and significant for the investment decision of the millennial generation in the era of society 5.0. The findings of this study indicate that if the millennial generation wants to improve their investment decisions in the era of society 5.0, they must improve their financial literacy and risk perception.